Information System Design COVID-19 with Prototype Model - Syahri Susanto; Julifer P. Manurung; Feddy Wnditya Setyawan (Buana Information Technology and Computer Sciences (BIT and CS), 2020)
Information System Design COVID-19 with Prototype Model